Infraspecific chemical variability of the leaf essential oil of Juniperus phoenicea var. turbinata from Portugal - Cavaleiro, Carlos (2001)
The essential oil composition of 68 individual plants of Juniperus phoenicea from Portugal was investigated by GC, GC-MS and 13C NMR. [alpha]-Pinene, [beta]-phellandrene, [alpha]-terpinyl acetate and myrcene were found to be the main constituents. Botanical and chemical data as well as phytogeographical distribution indicate J. phoenicea var. turbinata as the unique subspecies occurring in Portugal. Nevertheless, this taxon exhibits chemical polymorphism. The results of the oil compositions were processed by hierarchical clustering and principal component analysis allowing to establish three groups of essential oils differentiated by the content of [alpha]-pinene, [beta]-phellandrene and [alpha]-terpinyl acetate.